The Impact of Cochlear Implants and Aural Rehabilitation Program on Auditory Skills of Children with Cochlear Implant - Zahra Jeddi; Zahra Ja'fari; Masoud Motasaddi-Zarandi (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: Aural rehabilitation program after a cochlear implant leads to improve the auditory performance of hearing impaired children. The present study aims to determine the effect of cochlear implants and aural rehabilitation program in the auditory development of children with cochlear implants (CI). Materials & Methods: This longitudinal descriptive-analytical study was conducted on 15 deaf children (m.a. 45.27 mo) who received CI in the AmirAlam cochlear implant center between August 2010 and January 2011. Auditory skills of deaf children were assessed before they received CI, and also 2, 4, 6 and 8 months after implantation. Data was collected interview with parents of deaf children through Newsha developmental scale. After determining the developmental age, Pretest Developmental Rate, Intervention Efficiency Index and Proportional Change Index were calculated. One-way ANOVA and LSD post hoc tests were used for analysis of data. Results: There was a significant increase in Pretest Developmental Rate during the aural rehabilitation after a cochlear implantation (P<0.0001). There was a significant difference among the 4 follow up assessments of Intervention Efficiency Index (P<0.0001). There was also a significant difference among the 4 follow up assessments of proportional change index (P<0.0001). Conclusion: Aural rehabilitation program after a cochlear implant can accelerate the development of auditory skills of children with cochlear implants, which in turn results in promotion of acquired skills close to normal hearing peers